Assessment of the Impact of the Implementation of Electric Buses On the Amount of Emitted Harmful Emissions in the City of Sofia - Gatovski, Iliya (Research Papers, 2024)
The transport sector plays a key role in the development of modern cities, but at the same time it is one of the main sources of air pollution. In cities like Sofia, where air pollution is a serious problem, the modernization of public transport is imperative. This article analyzes the impact of the implementation of electric buses on the amount of emitted harmful emissions in Sofia, considering both the current data until 2024 and the forecasts for the next 3 – 7 years. A comparative analysis of data on harmful emissions before and after the introduction of electric buses is used to assess the impact. The data used are based on operating indicators from “Stolichne Autotrans” SHC and other sources such as “Center for Urban Mobility” EAD and the Metropolitan Municipality. The amounts of emissions of fine dust particles (PM10), carbon monoxide (CO), hydrocarbons (CxHx) and nitrogen oxides (NOx) were analyzed. A forecast scenario until 2030 is also made, based on current trends and planned initiatives.
Keywords: Electric buses; Harmful emission; Public transport